2020
DOI: 10.21203/rs.3.rs-46189/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Socioeconomic inequalities in hypertension in Kenya: A decomposition analysis of 2015 Kenya STEPwise survey on non-communicable diseases risk factors

Abstract: Background: One in four Kenyans aged 18–69 years have raised blood pressure. Despite this high prevalence of hypertension and known association between socioeconomic status and hypertension, there is limited understanding of factors explaining inequalities in raised blood pressure in Kenya. Hence, we quantified the socioeconomic inequality in hypertension in Kenya and decomposed the determinants contributing to such inequality.Methods: We used data from the 2015 Kenya STEPwise survey for non-communicable disea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
2
3
1
Order By: Relevance
“…Our study confirmed the minor pro-rich inequality of hypertension prevalence in Iran [15]. Studies report the pro-rich inequality of hypertension prevalence in the low-and middleincome countries such as Kenya [27] and China [28]. Yet, the magnitude of wealth-related inequalities in hypertension tends to be higher in poorer than in richer countries.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our study confirmed the minor pro-rich inequality of hypertension prevalence in Iran [15]. Studies report the pro-rich inequality of hypertension prevalence in the low-and middleincome countries such as Kenya [27] and China [28]. Yet, the magnitude of wealth-related inequalities in hypertension tends to be higher in poorer than in richer countries.…”
Section: Discussionsupporting
confidence: 85%
“…However, they included body mass index that explained 47% of variation in the inequality of hypertension. Most of the pro-rich inequality in hypertension control in Iran was explained by living in the urban area, complementary insurance, wealth index, and education, which confirms the established associations between health state and wealth status and education [27,30,31]. The underlying argument that explains such association is that wealth or income is materialized in resources such as nutrition and housing that affects health and wellbeing [32].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…First, we did not collect an income variable which some studies have recommended as a socioeconomic ranking variable. However, some surveys have indicated that household assets can be used as a proxy indicator for inequalities and it is sensitive to socioeconomic distribution [25, 37]. Second, we collected data from just two out of 10 provinces and therefore, generation of results may be limited.…”
Section: Discussionmentioning
confidence: 99%
“…)), social caste group (Scheduled Caste [SC], Scheduled Tribe [ST], Other Backward Caste [OBC], Other), household wealth quintile (poorest, poorer, middle, richer, richest), family history of high blood pressure, high glucose level and heart diseases (no, yes). These variables were decided based on the variable availability in the study data set and well-established literature [20,29,31,32,39,40,41].…”
Section: Independent Variablementioning
confidence: 99%